The relationship of academic service quality with student satisfaction of level 3 nursing study program at STIKes Santa Elisabeth Medan 2022 - Sarangih, Ice Septtriani; Rupang, Ernita Rante; Ginting, Friska; Manik, Marsalindah (International Journal of Nursing and Midwifery Research, 2023)
Quality of service is everything that focuses on services that are the needs and desires of student’s while satisfaction is a feeling of pleasure or disappointment that arises after a comparison process between student’s perceptions of performance or services provided to students, with the hope that students will be satisfied with the service the. services provided. Factors that influence student satisfaction are reliability, responsiveness, assurance, empathy and the last is tangible. Meanwhile, service quality is influenced by expected service and perceived service. This type of research is correlation using a cross sectional approach. Sampling using total sampling technique amounted to 85 respondents. The results showed that 56 respondents (65.9%) were satisfied with student satisfaction, while the quality of service they received was good with the results of 63 respondents (74.1%). The results of the Rank Spearman statistical test showed a value of p = 0.254, based on the research results obtained with a sample of 85 respondents, as many as (74.1%) of respondents got good quality academic services, while student satisfaction was obtained as many as (65.9%) of respondents and there is no significant relationship between service quality. It is recommended for future researchers to conduct research by looking for other factors that influence student satisfaction variables. factors such as physical evidence, reliability, responsiveness, empathy, and assurance